Peran Pendidikan Agama Islam dalam Membentuk Karakter Religius Siswa di SMP Al-Husna Cisalak - Siti Nuraziah; Silmi NiswaMaulida; Muhamad RiziqHaikal; Ajat Saputra (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
The role of Islamic Religious Education is very important in shaping the religious character of students in the school environment. This study aims to determine the extent of the role of Islamic Religious Education in shaping the religious character of students at SMP Al-Husna Cisalak. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the role of Islamic Religious Education at SMP Al-Husna is very influential in shaping the character of students. This can be seen from changes in the attitudes of students who are able to solve their own problems, respect their peers, are active in the learning process, and are consistent and confident in expressing opinions. Thus, Islamic Religious Education contributes significantly to shaping religious character which is reflected in the attitudes and behavior of students in everyday life.